Problem Failure of the Recidivist Guidance Program in Class I Prison Surabaya - Salsabila Oktaviani; Pudji Astuti (Universitas Negeri Surabaya, 2025)
The study is driven by the rise in recidivists in Surabaya's Class I Prisons during the 2022–2023 period. The rise in recidivism at Surabaya's Class I Prison suggests that the coaching program there has not been able to provide targeted guidance to recidivists. As mentioned in Article 2 of Law Number 22 of 2022 concerning Corrections, prisons serve as places where inmates receive guidance to ensure they do not commit crimes again. The purpose of this study is to identify the variables that lead to coaching failures in Surabaya's Class I Prison as well as the barriers that the prison faces in raising recidivists. This study employs qualitative, empirical legal research methods, gathering data through observation, interviews, and documentation, then analyzing it with descriptive analytical methods. The results of the research show that the Surabaya Class I Prison recidivism development program failed because prison officers were still unable to carry out their main responsibilities and the prison development program still carried out activities that were not in accordance with applicable laws and regulations, resulting in poor guidance and recidivism in Prisons Class I Surabaya .